Multiple ionization of atoms including post-collisional contributions - Montanari, Claudia Carmen (2012)
We present a theoretical study on multiple ionization on Ne and Kr by charged ions in the energy range (0.1-10) Mev/amu. We employed the continuum distorted-wave eikonal initial state and a Hartree-Fock description of the dressed-ion, together with photoionization branching ratios to include Auger-type post-collisional contributions. Results are good, especially for Kr targets. Some questions, such as limitations of the independent particle model or influence of the ion charge-state versus the ion nuclear-charge, are analyzed based on the different results for Ne and Kr targets. We found that single ionization is related to the ion charge-state while multiple-ionization shows that the nuclear-charge is weekly screened by the ion outer-electrons.